PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PEGAWAI POLITEKNIK ILMU PELAYARAN (PIP) - Moh. Zaenal Arifin (Dinamika Bahari, 2017)
As for target of which will reach in this research is to analysing cultural influence of organization to PIP Semarang officer Organizational Citizenship Behavior (OCB). Analysing organizational komitmen influence to PIP Semarang officer Organizational Citizenship Behavior (OCB). Pursuant to above mentioned background, hence researcher will test about cultural influence of organizational comitment and organization to officer Organizational Citizenship Behavior (OCB) in is PIP Semarang. Population in this research is PIP Semarang officer amounting to 319 one who consist of 215 PNS and 104 contract officer.To determine the amount of sample to be used as the source of information in this research is used by Slovin formula. Pursuant to result of calculation of determination of is amount of sampel with Slovin formula hence amount of minimum sampel which needed in this research is 178 PIP Semarang officer responder. Data which is used in research is primary data and secunder. Method analyse data use doubled linear regression analysis. Pursuant to result of research can be concluded by proven organizational culture have an effect on positively of significant to PIP Semarang officer Organizational Citizenship Behavior (OCB). Its Meaning, if organizational culture as according to individual values hence will push the make-up of employees Organizational Citizenship Behavior (OCB). Proven Organizational Comitment have an effect on positively of significant to PIP Semarang officer Organizational Citizenship Behavior (OCB). Its Meaning, if employees have strong organizational comitment hence this matter will push employees for have high Organizational Citizenship Behavior (OCB)